PENGEMBANGAN KETERAMPILAN DIGITAL KREATIF SISWA MELALUI WORKSHOP UI/UX DAN PROTOTYPING DENGAN FIGMA DI SMA ATHIRAH KAJAOLALIDO - Aras, Rezty Amalia; Furqan Zakiyabarsi; Aulia Rahmawati; Hany Alexandra; Muhammad Fachrul Salam (Nusantara Hasana Journal, 2026)
Strengthening creative digital literacy at the high school level is necessary so that students can design digital solutions relevant to user needs and possess basic UI/UX skills to build their portfolios and prepare for study and careers. This activity addressed these needs through a Figma workshop facilitated at Athirah Kajaolalido High School. The workshop used focus group discussions (FGDs) to map needs and design learning scenarios, followed by a two-day workshop. The first day consisted of design thinking and project design sessions. The second day focused on mentoring prototype creation in Figma. The activity resulted in 28 groups of 3–5 students each, producing ideas and prototypes on various themes (education, school services, productivity, the environment, and mental health). Pitching was assessed using eight indicators: problem analysis to solution, user flow, usability, visual aesthetics, design consistency, creativity, pitch structure, and engagement and delivery. The questionnaire results showed an average score of 4.46 for satisfaction with the material, usefulness of the material in helping solve problems, and ease of use of Figma, using a scale of 1–5. The Figma workshop effectively improved students’ basic understanding of the digital solution design process and their ability to produce prototypes and present ideas. A follow-up program with longer practice sessions and material reinforcement is recommended to optimize prototype quality and pitching skills.